Current opportunities of comprehensive therapy for bone metastases from thyroid cancer - A. P. Polyakov; P. O. Rumyantsev; P. A. Nikiforovich; A. V. Mordovsky; E. A. Chistyakova (Опухоли головы и шеи, 2020)
Background. Approximately 10 % of patients with well-differentiated thyroid cancer (WDTC) develop distant metastases. Of them, only 23 % have bone metastases. Complications associated with metastatic lesion in the skeleton significantly affect overall condition of patients and their quality of life. Surgery and pharmacotherapy are highly traumatic and toxic. Bisphosphonates are stable structural analogues of pyrophosphate that inhibit osteoclast activity, thereby reducing bone resorption, which increases the time to development of bone complications, improves patient’s quality of life, and reduces pain.The study objective is to assess performance status and pain severity in WDTC patients with distant bone metastases after bisphosphonate therapy.Materials and methods. We analyzed clinical experience in using bisphosphonates in WDTC patients treated in P.A. Herzen Moscow Oncology Research Institute between 2016 and 2020. This study included 41 patients with WDTC and bone metastases of various locations. Pain severity was evaluated using a 5-point verbal scale; performance status was evaluated using the Eastern Cooperative Oncology Group scale.Results. We observed an improvement in patients’ performance status (from score 2 to 0 according to the Eastern Cooperative Oncology Group scale) in response to therapy. We also found a decrease in pain intensity (from score 4 to 1.5).Conclusion. The inclusion of bisphosphonates into the treatment scheme for WDTC patients with bone metastases can reduce pain intensity and improve performance status.